Black-White Differences in the Reciprocal Relationship Between Perceived Discrimination and Psychological Distress. Issue 3 (3rd July 2022) - Oates, Gary; DeMaris, Alfred
ABSTRACT: We formulate a MIDUS longitudinal data-based multi-population LISREL model to gauge variation among Black and White Americans in the reciprocal relationship across time between perceived major and everyday discrimination, and psychological distress. Two hypotheses building on prior theory and empirical findings are generated: reciprocity between perceived discrimination and distress, and stronger reciprocity among Blacks . Here, "reciprocity" denotes positive effects of perceived discrimination and mental health problems such as distress on each other across time. Both hypotheses are supported for relationships between perceived everyday discrimination and distress. The model controls for several potentially relevant variables.